The Sports Day - Murray, William; Illustrated by Burton, Terry (London Ladybird Books)
Features a fun reading scheme that uses the 'look and say' approach to learning to read. This work is suitable for improving readers.
Include Color Illustrations
Stories by Jill Corby
Keywords: Sports -- Reading (Primary)